The Influence of Corporate Social Responsibility (CSR) on Company Value with Media Exposure as a Moderator - Widyastuti, Oviya; Cahyono , Edi (Institute of Accounting Research and Novation (IARN), 2024)
This research aims to determine the influence of Corporate Social Responsibility (CSR) on company value with media exposure as a moderator (Study of companies listed on the Jakarta Islamic Index 30 for the 2020 - 2022 period). This research uses quantitative research with secondary data. The data was processed using panel data multiple regression analysis using Eviews 9 software analysis. The research results show that Corporate Social Responsibility (CSR) has a significant positive effect on Company Value. Media Exposure has an insignificant positive effect. This research also found that media exposure can strengthen the influence of Corporate Social Responsibility (CSR) on company value with positive and significant results.